Transparency of data on the value chain of medicines in Argentina, Brazil, and Colombia - Ribeiro, Alane Andrelino; Acosta, Angela; Pontes, Marcela Amaral; Machado Beltran, Manuel Alejandro; Peixoto, Rafaela Tavares; Leite, Silvana Nair (Frontiers in Pharmacology, 2023)
Introduction: The transparency of data on the value chain of medicines is crucial for the study and monitoring of the pharmaceutical system. It may impact medicines´s pricing negotiations, contribute to people's access to pharmaceutical products and strengthen public health systems. Objective: This article analyses the national strategies to ensure the transparency of data from medicines cost development to marketing in Argentina, Brazil and Colombia. Method: A descriptive study was carried out by searching databases, contents of reports, documents and scientific articles between january and august 2022 related to the rules on transparency and databases available about 1) Marketing authorization; 2) Pricing; 3) Intellectual property; 4) clinical trials; 5) Research & Development (R&D) and 6) Health Technology Assessment (HTA) of selected biopharmaceuticals. Results: Transparency data, rules and information are not uniform. We provide evidence that as for infostructure (organizational capacity for collecting and distributing information) about the pharmaceutical value chain, the three countries face limitations to take appropriate measures to publicly share data and evidence about the pre-clinical, clinical data and costs. None require transparency about data on research and development costs. All the countries present similar publicization of data on marketing authorization and intellectual property, with the due peculiarities. Argentina presents important limitations, such as the absence of formal price regulation and of data on volume of purchases of medicines and respective amounts paid. Brazil, among the three, presents a higher degree of information transparency, perhaps due to the legal regulation that guarantees citizens access to information of public interest. This country stands out especially in terms of publicity of HTA reports and pricing, in addition to the highest volume of information. Colombia, on the other hand, drew attention to a decree that determines 5 years of trials data exclusivity for new medicines, going against data transparency. Despite the different stages of transparency, no country has shown a robust use of these data in public policy decision-making. Conclusion: information asymmetry between stakeholders, data fragmentation, data gaps and overlapping, and difficulty in comparing available data across the three countries, and also to the use of data nationally to produce evidence.